Ukraine : Technical Assistance Report-Tax Administration Reforms and Governance Options. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2016)
Immediate revenue measures need to be balanced with some attention to more fairness in tax collection. The mission recommends to cease revenue deferral arising from trivial tax disputes by requiring at least a partial payment of disputed tax before the appeal goes forward; collect tax arrears by promoting installment arrangements that fit the crisis conditions; strengthen routine monitoring of filing and payment obligations to control tax discipline; and make mandatory that largest taxpayers deal with their tax affairs at the large taxpayer inspectorate (LTI) offices instead of local offices. Ineffective internal dispute resolution processes should be replaced with an independent and fairer administrative review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet